Pemutusan Sepihak Oleh Pt Sumber Alfaria Trijaya Tbk. (Alfamart) Terhadap Perjanjian Kerja Sama Pengelolaan Parkir Dengan Cv Hulubalang Satu Ditinjau Dari Asas Itikad Baik - Soheri Soheri; Herawan S; Widiya N. Rosari (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study examines the unilateral termination by PT Sumber Alfaria Trijaya Tbk. or Alfamart of the parking management cooperation agreement with CV. Hulubalang Satu, reviewed from the principle of good faith in contract law. The issues discussed in this study focus on the legal status of the parking management cooperation agreement and the legal consequences of the unilateral termination carried out by Alfamart due to the provisions issued by the Bengkulu City Government concerning parking management. This research uses a normative legal research method with statutory and conceptual approaches. The legal materials consist of primary, secondary, and tertiary legal materials, which are analyzed qualitatively. The results show that the parking management cooperation agreement remains legally binding as long as it fulfills the validity requirements of an agreement as stipulated in Article 1320 of the Indonesian Civil Code. The unilateral termination by Alfamart cannot automatically be classified as an act contrary to the principle of good faith, as it was carried out as a form of compliance with the provisions of the Bengkulu City Government. As a legal consequence, the agreement cannot be continued if its implementation is no longer in accordance with the applicable regional legal provisions. However, the termination of the agreement must still consider the principles of propriety, reasonable notice, and legal protection for the party that has performed its obligations under the agreement.